Evaluation of Anthropometric Measurements with Sociodemographic Characteristics and Nutritional Status of Female Health Professionals - Erzurum Allim , Nural; Antıcı Çolak , Gözde; Karakaya, Rahime Evra; Dündar, Selin (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2020)
ABSTRACT This study was planned to evaluate the anthropometric measurements with sociodemographic characteristics and nutritional status of 134 women health professionals aged 20-50 years. Food frequency questionnaire form was applied by a trained dietitian for assessment of dietary intake. Anthropometric measurements such as body weight, height, waist circumference and hip circumference were taken. Physical activity status was determined by a one-day physical activity registration form. According to the BMI classification, 39.6% of women were overweight and 14.2% of them were obese. Daily carbohydrate intake was higher in normal weight (48.3%) than obese individuals (41.4%) (p<0.05). The prevalence of obesity is high among female health professionals. Unbalanced dietary macronutrient composition like low carbohydrate/high fat intake may lead to obesity.